Technologies Employed in the Treatment of Water Contaminated with Glyphosate: A Review - Patricio J. Espinoza-Montero; Carolina Vega-Verduga; Paulina Alulema-Pullupaxi; Lenys Fernández; Jose L. Paz (Molecules, 2020)
Glyphosate [N-(phosphonomethyl)-glycine] is a herbicide with several commercial formulations that are used generally in agriculture for the control of various weeds. It is the most used pesticide in the world and comprises multiple constituents (coadjutants, salts, and others) that help to effectively reach the action’s mechanism in plants. Due to its extensive and inadequate use, this herbicide has been frequently detected in water, principally in surface and groundwater nearest to agricultural areas. Its presence in the aquatic environment poses chronic and remote hazards to human health and the environment. Therefore, it becomes necessary to develop treatment processes to remediate aquatic environments polluted with glyphosate, its metabolites, and/or coadjutants. This review is focused on conventional and non-conventional water treatment processes developed for water polluted with glyphosate herbicide; it describes the fundamental mechanism of water treatment processes and their applications are summarized. It addressed biological processes (bacterial and fungi degradation), physicochemical processes (adsorption, membrane filtration), advanced oxidation processes—AOPs (photocatalysis, electrochemical oxidation, photo-electrocatalysis, among others) and combined water treatment processes. Finally, the main operating parameters and the effectiveness of treatment processes are analyzed, ending with an analysis of the challenges in this field of research.